[OP.2A.03] PROTEOMIC ANALYSIS REVEALS ALTERED PATHWAYS FROM EARLY STAGES OF THE DEVELOPMENT OF HYPERTENSIVE NEPHROPATHY IN SHR. (September 2017) - Hatziioanou, D.; Barkas, G.; Critselis, E.; Zoidakis, J.; Drossopoulou, G.; Charonis, A.; Vlahakos, D.V.
Abstract : Objective: Hypertensive nephropathy, a leading cause of declining kidney function is a multi-factorial process not well understood. Therefore system biology approaches should be adopted for a better understanding of the molecular pathways involved. Design and method: Proteomics studies were performed using the renal parenchyma of spontaneously hypertensive rats (SHR) and their normotensive counterparts Wistar Kyoto (WKY) rats. Animals were sacrificed at early time intervals (6, 13, and 20 weeks after birth), renal tissue extracts were subjected to two-dimensional gel electrophoresis, differentially expressed proteins were identified and altered pathways were evaluated by using Ingenuity Pathway Analysis. Results: The SHR group of animals reached and maintained mean BP of approximately 160–170 mmHg at all time intervals, while the WKY animals remained normotensive. As seen in the following Table, proteomic analysis revealed numerous spots with altered expression at 6, 13 and 20 weeks. Protein characterization followed by pathway analysis revealed that different processes are affected at different age. Figure. No caption available. Conclusions: Proteomic analysis followed by pathway analysis revealed that in the SHR model of hypertensive nephrosclerosis, early changes follow a pattern of progression from oxidative stress, mitochondrial dysfunction and receptor function to apoptosis pathways and alterations in cellular junctions. This work was supported from an ARISTEIA II grant (number 4045) to D. Vlahakos from the General Secretariat of Research and Technology of the Greek Ministry of Education.